POTENTIAL OF RICE STRAW AS A NATURAL FIBER MATERIAL FOR COMMERCIAL PRODUCTS - Lulu Fahriah Lihawa; Itsna Wafiyatul Izzah; Khairum Hawari Qolbiyah Siregar; Kurnia Syarafina Ramadhanti; Harum Azizah Darojati (Jurnal Forum Nuklir, 2021)
Cellulose is a material used in producing natural fibers, which is more environmentally friendly than synthetic fibers.Rice straw waste contains much cellulose and has potential as natural fiber.However, before the natural cellulose fiber is extracted from the rice straw, it must pass through several processes, such as chemicals or nuclear radiation, especially during the pretreatment process. Furthermore, the resulting natural fibers are utilized to replace synthetic fibers for use as raw materials in manufacturing several commercial products. This review describes a process that can be applied to manufacture natural fibers from rice straw and commercial products made from natural cellulose fibers.